Minimization of the programs total duration in flowshop production systems, without interruption in task execution - Branco, Fábio José Ceron; Nagano, Marcelo Seido; Moccellin, João Vitor (Revista Gestão da Produção Operações e Sistemas, 2008)
This paper addresses the m-machine no-wait flow shop scheduling problem to minimize makespan. The new method is compared with other improvement strategies reported in the literature. Experimental results show that the new heuristic provides better solutions regarding both solution quality and computational effort. Keywords: heuristics methods, no-wait flowshop, Makespan.